2019
DOI: 10.1016/j.heliyon.2019.e02315
|View full text |Cite
|
Sign up to set email alerts
|

DPPH scavenging capacity of extracts from Camellia seed dregs using polyol compounds as solvents

Abstract: This study investigated the properties of extracts of Camellia oleifera Abel seed dregs, which were extracted using polyol compounds. Solvents employed to extract the Camellia seed dregs included water, methanol, ethanol, and polyol compounds. The examined properties included ultraviolet (UV) absorbance, total polyphenol content, total flavonoid content, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging efficiency as an antioxidant ability. The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 16 publications
0
13
0
2
Order By: Relevance
“…In addition, the purified flavonoids have stronger antioxidant effects than the crude extracts, which is related to the purity of flavonoids. After purification by macroporous resin, the antioxidant capacity of flavonoids from Glycyrrhiza glabra L. leaf was increased by 2–3 times [ 27 ]. The scavenging rates of DPPH and ABTS free radicals of 100 μg/mL purified flavonoids from Moringa oleifera leaves were 85.99% and 84.79%, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the purified flavonoids have stronger antioxidant effects than the crude extracts, which is related to the purity of flavonoids. After purification by macroporous resin, the antioxidant capacity of flavonoids from Glycyrrhiza glabra L. leaf was increased by 2–3 times [ 27 ]. The scavenging rates of DPPH and ABTS free radicals of 100 μg/mL purified flavonoids from Moringa oleifera leaves were 85.99% and 84.79%, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The values are taken from average of triplicates measurements. Previous studies have showed that phenol is one of the major plant compounds with antioxidant activity [24]. It was reported that the antioxidant activity of phenolic and polyphenolic compounds was mainly due to their redox properties, and they play an important role in absorbing and neutralizing free radicals, quenching singlet and triplet oxygen, or decomposing peroxides [24].…”
Section: Resultsmentioning
confidence: 99%
“…DPPH is a stable free radical that produces a purple solution in ethanol. It is reduced and decolorized in the presence of antioxidant molecules and is often used to evaluate free radical scavenging activities of antioxidants, such as natural and synthetic pure compounds and plant extracts [24]. The ability to scavenge free radicals can be demonstrated by the degree of discoloration of the sample or extract.…”
Section: Solution Stabilitymentioning
confidence: 99%
“…Etanol adalah pelarut golongan alkohol yang bersifat polar dan cenderung bersifat tidak selektif, sehingga dapat mengekstraksi berbagai jenis dan golongan metabolit sekunder dalam suatu simplisia, termasuk flavonoid dan senyawa fenolik (Swamy et al, 2015). Terdapat korelasi positif antara kandungan fenolik dalam suatu sampel dengan aktivitas antioksidannya (S. Kumar et al, 2014;Tsai & Lin, 2019).…”
Section: Hasilunclassified